(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2023)
COVID-19 has affected social and economic life in several countries and the educational system is no exception. In response to the prevalence of the pandemic, digital technology has become a critical addition to face-to-face interactions for educational purposes. This study aimed to design a self-directed assessment framework (SDAF) for clothing and textile technology (CTT) undergraduates for distance learning. The assessment framework derived its understanding from the key concepts constituting assessment as the broader construct associated with sub-constructs such as skills and rubrics. A mixed methods approach was used in which twenty students and four lecturers from four purposively selected universities in Zimbabwe participated. Curriculum documents were analysed to identify skills to be assessed. Focus group discussions with lecturers confirmed the skills identified and ascertained the rubric for assessment. The framework was validated using a pilot test and Likert administered to students. A content data analysis method was used. Results showed that students found the framework for self-directed assessment of the skills outlined in the curriculum document valuable. Future explorations will help determine the usefulness of a similar framework in the theoretic concepts of the CTT curriculum.